Taxable and Tax-Deferred Investing: A Tax-Arbitrage Approach - Huang, Jennifer (Review of Financial Studies, 2008)
[We analyze an intertemporal portfolio problem with both taxable and tax-deferred retirement accounts. Using a tax-arbitrage argument, we identify conditions under which the optimal location decision (where to place an asset) is separable from the allocation decision (how much to allocate to each asset). Investors place highly taxed assets in the tax-deferred account to maximize the tax benefit and adjust their taxable portfolios to achieve the optimal risk exposure. We show that the two-account problem can be reduced to a taxable-account-only problem. The results are robust to capital gains tax deferrals, consumption and contribution decisions, and stochastic tax rates.]